フォーカルジストニアに罹患したプロピアニストに対するスプリント療法の実践 - 渡部 喬之; 佐野 太基; 牧野 亜由美; 酒井 健; 川崎 恵吉 (作業療法, 2023)
要旨：今回，フォーカルジストニアに罹患したプロピアニストの女性を担当した．事例は40歳代右利きの女性で，国内でのコンサート活動を主に行うプロピアニストである．演奏時の手の様子は，徐々に右の中指と環指が屈曲傾向となり，代償指として示指，小指の過伸展を認め，演奏継続が困難であった．代償指の過伸展予防，ジストニア指の固定を目的としたスプリントを作成し，段階的にスプリント装着下での演奏練習を継続した結果，介入123日目にはほぼ正常な演奏が可能となった．スプリント療法を行うことで代償指の過度な収縮を抑制し，求心路への適切な感覚入力を繰り返したことが効果的であったと考える． 　We report a case of a professional pianist with focal dystonia. The patient was a right-handed woman in her 40s who mainly performed concerts. While performing, she gradually fl exed her right middle and ring fi ngers, leading to compensatory hyperextension of the index and little fi ngers, making it diffi cult for her to continue playing. To prevent hyperextension of the compensatory fi ngers, a splint was made to fi x the dystonic fi ngers, and the patient gradually resumed practicing while wearing the splint. We believe that the splint therapy eff ectively suppressed excessive contraction of the compensatory fi nger and provided appropriate sensory input to the aff erent pathways.